The epidemics of bovine spongiform encephalopathy and variant Creutzfeldt-Jakob disease: current status and future prospects - Smith Peter G. (The World Health Organization, 2003)
The large epidemic of bovine spongiform encephalopathy (BSE) in the United Kingdom has been in decline since 1992, but has spread to other countries. The extensive control measures that have been put in place across the European Union and also in Switzerland should have brought the transmission of BSE under control in these countries, provided that the measures were properly enforced. Postmortem tests on brain tissue enable infected animals to be detected during the late stages of the incubation period, but tests that can be performed on live animals (including humans) and that will detect infections early are urgently needed. The number of infected animals currently entering the food chain is probably small, and the controls placed on bovine tissues in the European Union and Switzerland should ensure that any risks to human health are small and diminishing. Vigilance is required in all countries, especially in those in which there has been within-species recycling of ruminant feed. Fewer than 150 people, globally, have been diagnosed with variant Creutzfeldt-Jakob disease (vCJD), but there are many uncertainties about the future course of the epidemic because of the long and variable incubation period. Better control measures are necessary to guard against the possibility of iatrogenic transmission through blood transfusion or contaminated surgical instruments. These measures will require sensitive and specific diagnostic tests and improved decontamination methods.